Alexis de Tocqueville and the liberal tradition - Constanza Mazzina (Civilizar, 2008)
The article tries to find inside Tocqueville´s thought his contributions to the liberal tradition, understanding that this tradition has been growing from time to time, thanks to the contribution of different persons, each one has contributed to give shape and to consolidate what now we call and know as “liberalism”.